Fatigue Properties of Plain Concrete under Triaxial Constant-Amplitude Tension-Compression Cyclic Loading - 宋玉普 曹伟 孟宪宏 (Journal of Shanghai University, 2005)
Fatigue tests were conducted on tapered plain concrete prism specimens under triaxial constant-amplitude tension-compression cyclic loading. The low stress of the cyclic loading was taken as 0.2fc and the upper stress ranged from 0.20ft to 0.65ft. Three constant lateral pressures were 0.1fc, 0.2fc and 0.3fc respectively. Based on the results, the three-stage evolution nile of the fatigue stiffness, maximttm(minimum) longitudinal strain and damage were analyzed, and a unified S-N curve to calculate fatigue strength factors was worked out. The results show that the fatigue strength and fatigue life under triaxial constant-amplitude tension-compression cyclic loading are smaller than those under uniaxial fatigue condition. Moreover, the secondary strain creep rate is related to the fatigue life, a formula for describing their relation was derived. The investigation of this paper can provide information for the fatigue design of concrete structures.